Pemahaman Literasi Digital Guru dan Implikasinya dalam Pembelajaran Berdiferensiasi - Nurhidayah, Wida; Rakhmat Riyadi, Arie; Maulidah, Neni (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2025)
This study aims to explore elementary school teachers’ understanding of digital literacy and its implications for differentiated instruction. Digital literacy is considered an essential competency in addressing the challenges of 21st-century education, particularly in developing learning that responds to students' individual needs. This research employed a literature review method using a descriptive analysis approach by examining scholarly articles, academic books, and relevant research reports. The findings reveal that teachers’ digital literacy encompasses not only technical skills in using technology but also cognitive and pedagogical aspects, such as critically evaluating digital information and designing adaptive technology-based instruction. Teachers with high digital literacy are more capable of developing flexible and varied learning strategies tailored to students’ learning profiles. Conversely, limited digital literacy hinders the implementation of effective differentiated instruction. This study recommends continuous professional development and supportive educational policies to enhance teachers' digital competencies, thereby fostering inclusive and technology-relevant learning environments.